2016
DOI: 10.1080/10903127.2016.1194932
|View full text |Cite
|
Sign up to set email alerts
|

Community Implementation of a Prehospital Spinal Immobilization Guideline

Abstract: Key informants described a convergence of factors as leading to the successful implementation of a prehospital spinal immobilization guideline. Lessons learned regarding how to overcome a tradition of competition and isolation to allow for success may be useful to other communities considering similar initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…One possible explanation is that SMR has done more than simply provide alternative assessment and treatment options: in considering the limitations of past practice, it has also shifted baseline assumptions of potential harms and benefits of treatment – implicitly granting permission for more widespread practice change. This view corresponds with earlier opinions of SI as over-used, un-necessary, or sub-optimal, [ 1 , 17 , 18 ] and respondents to this survey described exactly this shift in practice in terms of “less fear in the workplace…towards not utilizing SMR” and a move away from “gross over-treatment”. Whether this shift can be described as adequate correction or over-compensation remains to be seen.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…One possible explanation is that SMR has done more than simply provide alternative assessment and treatment options: in considering the limitations of past practice, it has also shifted baseline assumptions of potential harms and benefits of treatment – implicitly granting permission for more widespread practice change. This view corresponds with earlier opinions of SI as over-used, un-necessary, or sub-optimal, [ 1 , 17 , 18 ] and respondents to this survey described exactly this shift in practice in terms of “less fear in the workplace…towards not utilizing SMR” and a move away from “gross over-treatment”. Whether this shift can be described as adequate correction or over-compensation remains to be seen.…”
Section: Discussionsupporting
confidence: 86%
“…First, the connection between the views of frontline providers and patterns of treatment has not been widely researched. Some studies have reported feelings of skepticism towards the value of SI or SMR among EMS personnel in a variety of settings, [ 1 , 17 , 18 ] and others have described differences in treatment before and after the transition to SMR, [ 19 , 45 ] but the relationship between provider beliefs and treatment patterns deserves more exploration [ 46 ]. In the service being surveyed, there has been a decreasing trend in the number of treatments over the last decade [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Adelgais et al described how organisational and technical barriers impeded implementation of prehospital pain management guidelines [ 35 ]. Motivation of personnel and intensive education are associated with successful implementation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%